Efficacy and safety of rituximab in adult frequent-relapsing or steroid-dependent minimal change disease or focal segmental glomerulosclerosis: a systematic review and meta-analysis - Xue, Cheng; Yang, Bo; Xu, Jing; Zhou, Chenchen; Zhang, Liming; Gao, Xiang; Dai, Bing; Yu, Shengqiang; Mao, Zhiguo; Mei, Changlin; Xu, Chenggang (Clinical Kidney Journal, 2021)
Background The efficacy and safety of rituximab (RTX) in adult frequent-relapsing (FR) or steroid-dependent (SD) nephrotic syndrome (NS), including minimal change disease (MCD) or focal segmental glomerulosclerosis (FSGS), are still inconclusive. Methods We performed a systematic review and meta-analysis registered in  PROSPERO (CRD42019148102) by pooling data of cohort studies or case series on adult patients with difficult-to-treat NS. Steroid-resistant NS was excluded. The primary outcomes were the complete remission (CR) rate and the relapse rate. Partial remission (PR) rate, no response (NR) rate and adverse events were the secondary outcomes. A random-effects model was performed for all the outcomes. Results We included 21 studies involving 382 adult MCD/FSGS subjects with a median follow-up duration from 12 to 43 months. RTX treatment induced a pooled 84.2% CR rate [95% confidence interval (CI): 67.7–96.3%], while MCD patients had a high 91.6% CR rate and FSGS patients a moderate 43% CR rate. However, 27.4% (95% CI 20.7–34.5%) of the patients relapsed during the follow-up. The pooled PR and NR rates were 5.8% (95% CI 1.2–12.5%) and 5.2% (95% CI 0.0–15.0%), respectively. RTX was associated with trivial adverse events and good tolerance. Conclusions In summary, by pooling results of current pilot studies, RTX may be an effective and relatively safe alternative for most adult FR or SD MCD/FSGS to displace calcineurin inhibitors or prednisone in the hierarchy of treatment. More clinical trials comparing RTX with other immunosuppressants and concerning the long-term adverse events are needed.